Agriculture Crop Protection from Animal Ambush - R.V Manjunath; Gagana G J; J Yashwanth Reddy; K Souparni Kousthubha; Vinod Kumar Reddy (Journal of Electronic Design Engineering, 2023)
Automation plays a vital role in standardizing our lives. There’s been a demand for the web of things in several sectors like monitoring crops, surveying, mapping the field, and providing data to farmers for farm management. Most of the crops have been ruined by animal ambush. Farm crops are frequently destroyed by neighborhood animals including buffalo, cows, goats, birds, etc. For the farmers, this results in enormous losses. Farmers are unable to barricade entire fields or to patrol them around-the-clock. The crop yields in the agricultural sector are being reduced by attacks by wild animals. One of the most important issues affecting agriculture today is the need to restrict animals from entering agricultural land from the forest. This project aims to forestall the prospective vandalizations caused by animals. Inspecting these entities to scale back, we tend to make use of motion detection and digital image processing for animal recognition, a GSM module to come up with an alert message, and an ultrasound to distract animals. The microcontroller now emits an alarm to entice the animals out of the field and sends a text message to the farmer alerting him to the problem so he may respond by arriving at the scene if the animals don’t leave after hearing the alarm. This completely protects the crops from animals, preventing loss to farmers.